2010
DOI: 10.2337/db09-0185
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Circulating Progenitor Cell Number and Failed Mechanisms of Stromal Cell-Derived Factor-1α Mediated Bone Marrow Mobilization Impair Diabetic Tissue Repair

Abstract: OBJECTIVEProgenitor cells (PCs) contribute to postnatal neovascularization and tissue repair. Here, we explore the mechanism contributing to decreased diabetic circulating PC number and propose a novel treatment to restore circulating PC number, peripheral neovascularization, and tissue healing.RESEARCH DESIGN AND METHODSCutaneous wounds were created on wild-type (C57BL/J6) and diabetic (Leprdb/db) mice. Blood and bone marrow PCs were collected at multiple time points.RESULTSSignificantly delayed wound closure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
94
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 37 publications
12
94
1
Order By: Relevance
“…In accordance it was documented that diabetic humans and animals exhibit fewer numbers of circulating progenitor cells (PCs) at rest and in response to ischemia. This can be refered to reduced ability of CD34 +ve endothelial PCs to proliferate, differentiate and integrate into the vessel (29).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance it was documented that diabetic humans and animals exhibit fewer numbers of circulating progenitor cells (PCs) at rest and in response to ischemia. This can be refered to reduced ability of CD34 +ve endothelial PCs to proliferate, differentiate and integrate into the vessel (29).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of such a macrophage-derived factor is a primary challenge in this field, because it will eventually turn into a therapeutic target in "poor mobilizer" conditions, such as diabetes. On the basis of observations that hyperglycemia promotes myelopoiesis (20) and that diabetes alters macrophage populations (21) and is associated with a defective CXCL12 switch (11,12), in the study reported here we examined the role of BM macrophages (BMMF) in diabetic SC mobilopathy. We found an excess of proinflammatory macrophages in the diabetic BM and that macrophage depletion restores mobilization.…”
mentioning
confidence: 99%
“…In addition, because the BM is a reservoir of vascular regenerative cells, BM alterations may pave the way to multiorgan damage (2). On a molecular level, diabetes prevents the chemokine (C-X-C motif) ligand 12 (CXCL12) switch (11,12) (i.e., the suppression of intramarrow levels of the chemokine CXCL12 that normally allows stem cell mobilization) (13). Although a maladaptive response of the CXCL12-cleaving enzyme dipeptidyl peptidase-4 has been hypothesized (14), the exact mechanism perturbing a coordinated CXCL12 regulation in diabetes is unclear.…”
mentioning
confidence: 99%
“…Cutaneous wound site multicellular competence and engagement is essential for normal cytokine/ chemokine/growth factor dynamics that produce dermal tissue homeostasis. However, cellular deficiencies and disruption in diabetic wounds compromise this process and also elicit impaired angiogenesis and neovascularization associated with abnormal endothelial cell functions and vascular endothelial growth factor and stromal cellderived factor 1 bioactivities, contributing to the diabetic wound healing problem (5,6). Recent evidence demonstrates that bone marrow-derived progenitor cells are correlated with new blood vessel formation in wounds (7,8).…”
mentioning
confidence: 99%
“…Cutaneous injury mobilizes these progenitor cells from marrow, and resulting circulating progenitor cells then transport to injury sites, transmigrate into wounded tissue, and initiate repair functions, among them new vessel formation (7,9). While numbers of marrow-derived progenitors in diabetic and wild-type mice are relatively similar, reduced mobilized circulating progenitor cells are present in diabetic mice both before and after wounding (5). Harvesting marrow cells and adoptively transferring them, either topically or subcutaneously, into diabetic wounds overcomes impaired progenitor cell mobilization, injury homing, and migration.…”
mentioning
confidence: 99%